Relationship between cardiorespiratory fitness and latitude in children and adolescents: Results from a cross-sectional survey in China - Zhang, Ting (J Exerc Sci Fit, 2021)
BACKGROUND: This study assessed the correlation between latitude and the cardiorespiratory fitness (CRF) of children and adolescents. METHODS: In 16 provinces and autonomous regions in China, 25,941 children and adolescents aged 10–18 were included. CRF was measured using the 20 m shuttle run test (20 m SRT) and estimated peak oxygen uptake (VO(2peak)). One-way ANOVA and multiple regression analysis were used to explore the correlation between CRF and latitude in children and adolescents. RESULTS: The VO(2peak) values of the low (south), middle, and high (north) latitude groups for boys were 43.1, 43.1, and 40.7 mL/kg/min, respectively, and 40.0, 40.0, and 38.5 mL/kg/min for girls, respectively. After adjusting for confounding factors, the regression coefficients (β) between VO(2peak)-Z and both latitude-Z and (latitude-Z)(2) for boys were −0.151 and −0.043, respectively. For girls, they were −0.142 and −0.020, respectively. The Partial correlation coefficient (r) for latitude-Z and (latitude-Z)(2) were −0.14 and −0.04 for boys, and −0.13 and −0.02 for girls, respectively. CONCLUSION: The CRF among children and adolescents in high latitude regions is significantly lower than that in middle and low latitude region, and it generally shows a “parabolic” trend between Latitude-Z and VO(2peak)-Z.